Muscle activation of plantar flexors in response to different strike patterns during barefoot and shod running in medial tibial stress syndrome - Byungjoo Noh; Takeo Ishii; Akihiko Masunari; Yuhei Harada; Shumpei Miyakawa (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Medial tibial stress syndrome (MTSS) is one of the most common causes of exercise-induced lower leg pain in running athletes. The purpose of this study was to compare plantar flexor activation changes in response to different strike patterns during barefoot and shod running in subjects with and without MTSS. The changes were assessed by observing motion characteristics derived from mechanical factors. The 15 collegiate soccer players who volunteered to participate were divided into two groups (7 MTSS, 8 non-MTSS). Three-dimensional marker positions were recorded with a 12-camera motion capture system (Vicon) operating at 250 Hz while the subjects ran along a runway at 3.3 m/s. Each subject completed the running with and without shoes, and different strike patterns as the forefoot strike pattern (FFS) and rearfoot strike pattern (RFS) were collected. Plantar flexor activation was investigated by software for interactive musculoskeletal modeling (SIMM) based on how the activation ratio changed from 0 to 1 at landing. Compared to controls, the MTSS group had higher tendency muscle activity of the plantar flexors that involved the peroneal muscle during first half of stance (p <0.05). For the stance phase of running, the MTSS group had greater muscle activity during plantar flexion in running with the FFS pattern than running with the RFS pattern (p <0.05). These results suggest that subjects with MTSS have higher activity of the plantar flexors during running, especially with the FFS pattern, which suggests greater stress on soft tissues of the tibial portion and a tendency to develop MTSS.